2020
DOI: 10.3390/antiox9060552
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Derived Natural Biomolecule Picein Attenuates Menadione Induced Oxidative Stress on Neuroblastoma Cell Mitochondria

Abstract: Several bioactive compounds are in use for the treatment of neurodegenerative disorders, such as Alzheimer’s and Parkinson’s disease. Historically, willow (salix sp.) bark has been an important source of salisylic acid and other natural compounds with anti-inflammatory, antipyretic and analgesic properties. Among these, picein isolated from hot water extract of willow bark, has been found to act as a natural secondary metabolite antioxidant. The aim of this study was to investigate the unrevealed pharmacologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 61 publications
(74 reference statements)
0
30
1
Order By: Relevance
“…Several external and/or internal noxious stimuli are able to produce neuronal damage that in most occasions triggers an imbalance in the neuronal oxidative homeostasis, resulting in most cases in accumulation of oxygen free radicals that damage proteins, nucleic acids, and lipid membranes, leading to neuronal death [ 10 ]. To study neuronal dysfunction, we used a model based in the increase of endogenous reactive oxygen species (ROS) production, induced by the treatment of cells with the toxin menadione (VitK3) [ 14 , 15 , 16 ]. VitK3 is an exogenic toxin that produces mitochondrial damage linked to an increase in ROS [ 17 ], distorting cellular structures such as the endoplasmic reticulum, but also influencing important metabolic pathways such as glycolysis and/or pentose phosphate (PPP) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several external and/or internal noxious stimuli are able to produce neuronal damage that in most occasions triggers an imbalance in the neuronal oxidative homeostasis, resulting in most cases in accumulation of oxygen free radicals that damage proteins, nucleic acids, and lipid membranes, leading to neuronal death [ 10 ]. To study neuronal dysfunction, we used a model based in the increase of endogenous reactive oxygen species (ROS) production, induced by the treatment of cells with the toxin menadione (VitK3) [ 14 , 15 , 16 ]. VitK3 is an exogenic toxin that produces mitochondrial damage linked to an increase in ROS [ 17 ], distorting cellular structures such as the endoplasmic reticulum, but also influencing important metabolic pathways such as glycolysis and/or pentose phosphate (PPP) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Streptozotocin is a highly toxic compound that has been used not only for inducing type 1 diabetes in rodents [42] but can also stimulate sporadic AD in vivo [33]. On the other hand, menadione, a synthetic precursor of vitamin K2, is well known to cause DNA damage by inducing high reactive oxygen species generation (ROS) in vitro [36,43]. The MTT assay quantifies the mitochondrial activity.…”
Section: Discussionmentioning
confidence: 99%
“…For the experiments, the following treatment groups were taken: (1) control, (2) vitamin K2, (3) streptozotocin, (4) streptozotocin + vitamin K2, (5) menadione, and (6) menadione + vitaminK2. For each experiment, after 20-24 h of cell passage for proper cell adherence, cells were treated with varied concentrations of streptozotocin (1 mM, 1.5 mM, 2 mM, and 2.5 mM) for 24 h, followed by post-treatment of vitamin K2 at a fixed concentration of 50 µM for 5 h. In case of menadione-induced toxicity, cells were treated with varied concentrations of menadione (100 nM, 250 nM, 500 nM, 1 µM, and 10 µM) for 2 h as standardized previously [36], followed by post-treatment of a fixed concentration of vitamin K2 for 5 h. All experiments were performed in triplicate to quadruplet. All the experiments were performed after treatment with vitamin K2 and all the data presented are blank corrected.…”
Section: Experimental Design For In Vitro Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another recent in vivo study on rats has reported successful mitigation of the adverse effects of doxorubicin (DOX) by p-CA, which also acts as an aphrodisiac agent in the treatment of erectile dysfunction (ED) [ 21 ]. Plant-derived compounds have always been of interest to researchers for the development of new drugs and for the management of various human diseases [ 22 ]. p-CA could be a promising candidate for use as a drug against several diseases, particularly characterized by oxidative stress.…”
Section: Introductionmentioning
confidence: 99%